TITIK TETAP PERSEKUTUAN EMPAT PEMETAAN KONTRAKTIF PADA RUANG METRIK CONE - Ainal Mawaddah; Muhammad Mahfuzh Shiddiq; Nurul Huda (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2019)
called cone metrics. A non-empty set X with a metric cone d is called cone metric space. A mapping has a unique fixed point if the mapping is contractive mapping. The concept of a fixed point of fellowship in the cone metric space must also satisfy some coincidence point, point of coincidence, and weakly compatible mapping conditions. This study examines the fixed point of fellowship for four contractive mappings in the cone metric space. The result of this study indicate that four mapping S, T, I and J have a unique fixed point of association in the cone metric space.Keywords: cone metric space, common fixed point,contractive mapping, coincidence point, point of coincidence, weakly compatible.